LATAR BELAKANG SEJARAH DAN PERTIMBANGAN LOKASI PERMUKIMAN CANDI BARU DI SEMARANG - S.S, Harriyadi; Jauharatna, Kartynada; Nugroho, Dimas; Bismoko, Dimas Seno; Syofiadisna, Panji; Mahardian, Dewangga Eka (AMERTA, 2023)
Abstract. The Historical Background and Site Consideration Candi Baru Settlement in Semarang. Semarang is a port city in Java that had rapid development during the late Colonial era. The city has developed into an industrial and administrative center since the Dutch influence in the archipelago. The growth of job opportunities led to an increase in the urbanization rate as people moved to Semarang. The Area of Candi Baru Settlement was developed in the 1900th by the Dutch colonial government, located south of Semarang in Gajahmungkur Hill, which is quite far from the city and in the hilly area. This study aimed to determine the historical background and considerations for selecting the location of the Candi Baru Settlement during the Colonial period. The data used in the research include old maps to understand the development of the settlement and its environmental context, as well as literature data such as historical archives to explore its social and political aspects. The qualitative analysis was carried out by connecting historical data with environmental data to identify the environmental factors and colonial government intervention. The results of this study indicate that poor ecological sanitation, disease outbreak, and population mortality rates are the driving factors for the opening of settlements south of Semarang City. Gajahmungkur Hills provides an alternative healthy living environment and is comfortable for its residents. Keywords: Candi Baru, Semarang, Settlement   Abstrak. Semarang adalah kota pelabuhan di Pulau Jawa yang cukup pesat perkembangannya pada era akhir Kolonial. Semarang tumbuh menjadi pusat perdagangan dan industri sejak ditetapkan sebagai kota praja. Berkembangnya lapangan pekerjaan berdampak pada meningkatnya laju urbanisasi penduduk menuju Semarang. Area Permukiman Candi Baru dikembangkan pemerintah kolonial Belanda pada tahun 1900-an, yang terletak di sebelah selatan Semarang, tepatnya di Bukit Gajahmungkur. Lokasinya terbilang cukup jauh dari pusat Kota Semarang dan berada pada area bukit. Penelitian ini bertujuan untuk mengetahui latar belakang sejarah dan pertimbangan pemilihan lokasi Permukiman Candi Baru Semarang pada masa Kolonial. Data yang digunakan berupa peta lama untuk mengetahui perkembangan permukiman dan konteks lingkungannya serta data pustaka berupa arsip-arsip sejarah untuk mengetahui aspek sosial, politik, dan lingkungan yang melatarbelakanginya. Analisis dilakukan secara kualitatif dengan mengaitkan data sejarah dengan lingkungan sehingga dapat diperoleh faktor pertimbangan lingkungan dan intervensi yang dilakukan oleh pemerintah kolonial. Hasil penelitian ini menunjukkan buruknya sanitasi lingkungan, wabah penyakit, dan tingginya angka kematian penduduk di Kota Semarang sebagai faktor pendorong dibukanya permukiman baru di sebelah selatan Kota Semarang. Bukit Gajahmungkur memberikan alternatif lingkungan tempat tinggal yang sehat dan nyaman para penghuninya. Kata Kunci: Candi Baru, Permukiman, Semarang